Pasting profiles and gel properties of rice flour blended with native, cross-linked, and acetylated tapioca starch - Wongkhueng Kanyapat; Thumthanaruk Benjawan; Wandee Yuree; Lamsal Buddhi; Rungsardthong Vilai (E3S Web of Conferences)
The pasting properties of rice starch can be improved by blending it with native or modified starch. This research investigated the pasting profiles and gel properties of rice flour (RF) blended at different concentrations with tapioca starch (TS), lowand highdegrees of crosslinked starch (LCL and HCL), and lowand highdegrees of substitution of acetylated starch (LAC and HAC). The results showed that substituting RF with both native and modified starches tended to decrease the pasting temperature of the flour blends. The increase in HCL in flour blends resulted in a higher pasting temperature, final viscosity, and setback. At the same time, adding LAC and HAC did not affect the pasting temperature, but a significantly decreased final viscosity was observed. RF-HCL10 and RF-HAC10 exhibited significantly higher swelling power than RF alone. Blending RF with HCL at 5, and 10% by weight could improve the freeze-thaw stability of the gels made from each blend. The information obtained herein is useful for the prediction of product properties that are rich in starch.